Benign and precursor lesions in the esophagus. (29th September 2014) - Akiyama, Junichi; Bertelé, Anna; Brock, Christina; Hvid‐Jensen, Frederik; Ichiya, Tamaki; Krarup, Anne Lund; Majewski, Marek; Rubio, Carlos A.; Sarosiek, Jerzy; Scarpignato, Carmelo; Schmidt, Peter Thelin; Teich, Steven; et al.
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the role of salivary stimulation and esophageal secretion of protective factors in prevention of adenocarcinoma sequelae in gastroesophageal reflux disease; the pediatric conditions associated with esophageal cancer; the relationship of achalasia and pseudoachalasia with esophageal cancer; the potential for malignant transformation in eosinophilic esophagitis and overlap syndromes; the role of lymphocytic esophagitis as an overlapping phenotype; the role of Barrett's esophagus as a premalignant condition; the indications and type of treatment of premalignant conditions of the esophagus; and the decision for use of endoscopical procedures in premalignant conditions of the esophagus.